IMPLEMENTASI TEKNIK IMPROVISASI BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN EKSPRESI DIRI SISWA TEATER DI SMPK SWASTA JAKARTA - Petrisia Sabattani; Jaeni; Yahfenel Evi Fuhsalam (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Contemporary formal theatre arts education tends to focus on conventional techniques and rigid scripts, which significantly limit students' exploration, creativity, and spontaneity at the secondary school level. Consequently, students' self-confidence and self-expression are often sub-optimally developed. This study aims to develop and validate structured improvisation techniques within the theatre arts curriculum to enhance students' self-expression, employing a Research and Development (R&D) approach with a case study location at a private Christian Junior High School (SMPK Swasta) in Jakarta. Qualitative methods, including participatory observation and in-depth interviews, were utilized, with data analysis conducted through the Miles & Huberman model. The intervention focused on the "Practice – Express – Reflect – Revise" Cycle Model, integrating Spolin's Theater Games with local Ketoprak wisdom adaptations: the "Kata Berkait" (Chain Word) and "Udar Rasa" (Airing of Emotion) techniques. Findings indicate that the structured implementation of improvisation techniques successfully enhanced students' verbal and non-verbal expression, spontaneity, and self-confidence significantly. This reflective learning model proved effective in overcoming performative anxiety and curricular rigidity, serving as a vital "expression laboratory" for 21st-century soft skill development. It is recommended that improvisation be integrated as a core component of the theatre arts curriculum to foster a more authentic and empowering learning experience.